Influence of the mobility package on the functioning of the Polish road transport of goods sector - Suproń, Błażej (Wpływ pakietu mobilności na funkcjonowanie polskiego sektora transportu drogowego towarów, 2020)
The article presents the results of the introduction of the provisions suggested by the European Union’s legislative authorities with regard to transport market regulation, referred to as the Mobility Package. The business of enterprises is based on planning, both in the short and long term, business decisions are made in advance, and internal and external factors taken into consideration. To emphasize the importance of the issues discussed, it is worth noting that the regulations under study constituted the first such in-depth change of the market since Poland joined the European Union. An earlier analysis of the solutions suggested allows enterprises to get ready for the upcoming changes and to take appropriate decisions to minimize their effects, if any. Consequently, the purpose of this paper was to attempt to assess the impact of the Mobility Package on the Polish road transport industry. To study this goal it was necessary to gather and analyse extensive research material originating from official statistical data, industry reports and scientific publications of domestic and foreign authors. The methodology of the research included analysis of the scientific literature, European Commission documents and statistical data analysis
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 3, s. 92-106
Keywords: road freight transport; Mobility Package; minimum wage; transport market; dispatching drivers; transport drogowy łańcuchowy; Pakiet Mobilności; płaca minimalna; rynek transportowy; delegowanie kierowców